2014
DOI: 10.1007/s11136-014-0755-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to develop a patient-reported outcome for dysmenorrhea

Abstract: The eDiary was conceptually comprehensive and easy to complete/understand during cognitive debriefing. The resulting nine-item diary included assessment of: menstrual bleeding severity; pain severity; use of analgesics; impact on work/school, physical activities, social and leisure activities, and sleep. Psychometric validation is ongoing and will assess the reliability, validity, and responsiveness of the eDiary as a comprehensive dysmenorrhea assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
3
30
0
7
Order By: Relevance
“…Abdominal pain intensity is typically the only symptom assessed in dysmenorrhea [26]. Yet consistent with previous studies [16, 22], we found that many participants experienced pain at multiple sites and reported a variety of gastrointestinal symptoms. Previous studies have reported that increased prostaglandins and pain sensitization among women with dysmenorrhea are likely to contribute to pain at multiple sites and gastrointestinal symptoms [3, 11, 27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Abdominal pain intensity is typically the only symptom assessed in dysmenorrhea [26]. Yet consistent with previous studies [16, 22], we found that many participants experienced pain at multiple sites and reported a variety of gastrointestinal symptoms. Previous studies have reported that increased prostaglandins and pain sensitization among women with dysmenorrhea are likely to contribute to pain at multiple sites and gastrointestinal symptoms [3, 11, 27].…”
Section: Discussionsupporting
confidence: 90%
“…Our study along with others focusing on endometriosis [19, 22] demonstrate that dysmenorrhea symptoms interfere with daily life in a variety of domains (e.g., physical, occupational, recreational, and relational). Such domains are included in interference scales in available instruments such as the Brief Pain Inventory [30] and the Patient-Reported Outcomes Measurement Information System (PROMIS®) [31].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A pesar de la alta prevalencia, muchas mujeres no buscan asesoramiento profesional porque consideran que es una parte normal del ciclo menstrual (Iacovides et al, 2015;Kumar K et al, 2016) y las que deciden iniciar un tratamiento lo hacen de manera deficiente (Harel, 2008). En este sentido, los autores coinciden en que la dismenorrea primaria tiene un importante impacto en la calidad de vida de las mujeres (Iacovides et al, 2015;Kumar K et al, 2016;Al-Jefout et al, 2015;De Sanctis et al, 2016;Hoppenbrouwers et al, 2016;Iacovides, Avidon, Bentley, & Baker, 2014;Kennett, O'Hagan, & Meyerhoff, 2016;Knox, Azurah, & Grover, 2015;Nguyen, Humphrey, Kitchen, Rehman, & Norquist, 2015;Nur Azurah, Sanci, Moore, & Grover, 2013;Osayande & Mehulic, 2014;Rani, Sharma, & Singh, 2016;Sahin, Kasap, Kirli, Yeniceri, & Topal, 2018;Wong, 2018) especialmente en las adolescentes (Knox et al, 2015;Nur Azurah et al, 2013). Es la causa más frecuente de la reducción de la productividad laboral (Ju et al, 2014), del rendimiento académico, así como de la disminución de las actividades sociales, físicas y deportivas de las mujeres (Kumar K et al, 2016).…”
Section: Introductionunclassified
“…Having identified an absence of patient-reported outcome measures in dysmenorrhoea, a group of researchers recently sought to develop a new measure that could be used in clinical trials. 2 Openended interviews with 52 women who suffered from dysmenorrhoea revealed that pain in the pelvic region was the most important symptom and despite rescue medication use, it often had a significant impact on many aspects of their lives. Interview data guided the production of a conceptual eDiary that includes assessment of menstrual bleeding severity, pain severity, use of analgesia, impact on school/work activities, physical activities, social activities, and sleep.…”
mentioning
confidence: 99%